Immunity-related GTPases (IRGs) in the house mouse and the parasite Toxoplasma gondii in South America - Alvarez, Catalina (2021)
"The Immunity-related GTPases (IRGs) are IFNγ-inducible genes essential for resistance against intracellular pathogens in the house mouse. In some wild-derived house mice, such as the Eurasian mice CIM strain, polymorphic IRG genes have been linked to the control of virulent strains of the intracellular parasite Toxoplasma gondii. The house mouse (Mus musculus domesticus) arrived in the Americas on the first European vessels in the 16th century, but they had never encountered infections with the highly virulent T. gondii strains present in South America.(...)"